The SoLid anti-neutrino detector's readout system - Arnold, L; Beaumont, W; Cussans, D; Newbold, D; Ryder, N; Weber, A; SoLid Collaboration (Institute of Physics, 2017)
The SoLid collaboration have developed an intelligent readout system to reduce their 3200 silicon photomultiplier detector's data rate by a factor of 10000 whilst maintaining high efficiency for storing data from anti-neutrino interactions. The system employs an FPGA-level waveform characterisation to trigger on neutron signals. Following a trigger, data from a space time region of interest around the neutron will be read out using the IPbus protocol. In these proceedings the design of the readout system is explained and results showing the performance of a prototype version of the system are presented.